Real wage rigidities and the new Keynesian model - Olivier Blanchard; Jordi Galí (Federal Reserve Bank of Boston, 2005)
Most central banks perceive a trade-off between stabilizing inflation and stabilizing the gap between output and desired output. However, the standard new Keynesian framework implies no such trade-off. In that framework, stabilizing inflation is equivalent to stabilizing the welfare-relevant output gap. In this paper, we argue that this property of the new Keynesian framework, which we call the divine coincidence, is due to a special feature of the model: the absence of nontrivial real imperfections. We focus on one such real imperfection, namely, real wage rigidities. When the baseline new Keynesian model is extended to allow for real wage rigidities, the divine coincidence disappears, and central banks indeed face a trade-off between stabilizing inflation and stabilizing the welfare-relevant output gap. We show that not only does the extended model have more realistic normative implications, but it also has appealing positive properties. In particular, it provides a natural interpretation for the dynamic inflation-unemployment relation found in the data.
Keywords: E32; E50; 330; oil price shocks; inflation targeting; monetary policy; inflation inertia; Reallohn; Lohnrigidität; Arbeitslosigkeit; Geldpolitisches Ziel